Selected Court Cases /á‹¨á‰°áˆ˜áˆ¨áŒ¡ ááˆá‹¶á‰½ - Chane, Gizachew Silesh (Bahir Dar University Journal of Law, 2022)
These case reports initially originated from the decisions of the courts from Amhara Regional State and then reviewed by the Federal Supreme Court Cassation Division. The First case concers period of limitations on land in which the controversy is when the period of limitation begins to count, from the time of possession or from the time the possesser claims certificate of heirship. The case is finally settled in that period of limitation begins to count from the time the possessor took possession. The second case concern whether house allowance should be subject to taxation. The final settlement is that house allowance is part of employement income and in the abscence explicit exemption, it is subject to income tax deduction.